Impact of combinations of single-nucleotide polymorphisms of anthracycline transporter genes upon the efficacy and toxicity of induction chemotherapy in acute myeloid leukemia. Issue 3 (23rd February 2021) - Megías-Vericat, Juan Eduardo; Martínez-Cuadrón, David; Herrero, María José; Rodríguez-Veiga, Rebeca; Solana-Altabella, Antonio; Boluda, Blanca; Ballesta-López, Octavio; Cano, Isabel; Acuña-Cruz, Evelyn; Cervera, José; Poveda, José Luis; Sanz, MiguelÁngel; et al.
Abstract: Anthracycline uptake could be affected by influx and efflux transporters in acute myeloid leukemia (AML). Combinations of single-nucleotide polymorphisms (SNPs) of wild-type genotype of influx transporters ( SLC22A16, SLCO1B1 ) and homozygous variant genotypes of ABC polymorphisms ( ABCB1, ABCC1, ABCC2, ABCG2 ) were evaluated in 225 adult de novo AML patients. No differences in complete remission were reported, but higher induction death was observed with combinations of SLCO1B1 rs4149056 and ABCB1 (triple variant haplotype, rs1128503), previously associated with ABCB1 and SLCO1B1 SNPs. Several combinations of SLCO1B1 and SLC22A16 with ABCB1 SNPs were associated with higher toxicities, including nephrotoxicity and hepatotoxicity, neutropenia, previously related to ABCB1, and a novel correlation with mucositis. Combination of SLC22A16 rs714368 and ABCG2 rs2231142 was related to cardiac toxicity, reproducing previous correlations with ABCG2 . This study shows the impact of transporter polymorphisms in AML chemotherapy safety. Further prospective studies with larger populations are needed to validate these associations.